In which step did we first make a mistake?

\[ \begin{array} { l l l }

0 & = \displaystyle \sum_{i=0}^\infty 0 & (1) \\
& = \displaystyle \sum_{ i=0}^ \infty (1 -1) & (2) \\
& =\displaystyle \sum_{ i=0}^ \infty 1 - \displaystyle \sum_{i=0}^\infty 1 & (3) \\

& = \left ( 1 + \displaystyle \sum_{ {\color{red}i=1}}^ \infty 1\right) - \displaystyle \sum_{j=0}^\infty 1 & (4) \\

& = 1 +\displaystyle \sum_{ j=0}^ \infty 1 - \displaystyle \sum_{j=0}^\infty 1 & (5) \\

& = 1 +\displaystyle \sum_{ j=0}^ \infty (1 - 1) & (6) \\

& = 1 & (7) \\
\end{array} \]

×

Problem Loading...

Note Loading...

Set Loading...